2008
DOI: 10.1351/pac200880112273
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis at the interface of nano-oxides and nanozeolites

Abstract: The catalysts that can efficiently hydro-reform higher n-paraffin to lower isoparaffins for environmentally friendly gasoline were studied. The catalysts were examined by the conversion of n-hexadecane, n-C 16 H 34 to i-C 6 H 14~i -C 12 H 26 . The tri-modally nanoporous (nanometer-size) catalysts composed of (Ni-Mo)/[γ-Al 2 O 3 ], nano-oxide, and nanocrystalline zeolite have some active and selective performances because of the cooperation between (Ni-Mo)/[γ-Al 2 O 3 ] and the composite of nano-oxide-nanozeoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…This indicates that a concerted reaction occurs on the three-component catalyst. Just like for a three-component catalyst containing USY zeolite (NiMo/γ-Al2O3 _ ns Al2O3 _ USY zeolite) 32) , a combined effect was confirmed for a threecomponent catalyst containing beta zeolite (NiMo/ γ-Al2O3 _ ns Al2O3 _ beta zeolite). Moreover, the threecomponent catalyst containing beta zeolite has a higher cracking activity and a higher selectivity despite beta zeolite having a higher SiO2/Al2O3 molar ratio (approximately 25) than USY zeolite (about 12).…”
Section: Combined Effect Of Catalyst Components Onmentioning
confidence: 64%
See 3 more Smart Citations
“…This indicates that a concerted reaction occurs on the three-component catalyst. Just like for a three-component catalyst containing USY zeolite (NiMo/γ-Al2O3 _ ns Al2O3 _ USY zeolite) 32) , a combined effect was confirmed for a threecomponent catalyst containing beta zeolite (NiMo/ γ-Al2O3 _ ns Al2O3 _ beta zeolite). Moreover, the threecomponent catalyst containing beta zeolite has a higher cracking activity and a higher selectivity despite beta zeolite having a higher SiO2/Al2O3 molar ratio (approximately 25) than USY zeolite (about 12).…”
Section: Combined Effect Of Catalyst Components Onmentioning
confidence: 64%
“…They are generated when Si _ OH in the nanopores of the USY zeolite produced by dealumination traps Al _ OH in the ns Al2O3 precursor. On the other hand, we found that catalysts composed of beta zeolite or ZSM-5 (hereafter, MFI) zeolite are activated more by ns SiO2 than ns Al2O3 and that they have higher activities than a catalyst composed of USY zeolite 32) . Overcracking that produced a gaseous component was observed when a catalyst composed of MFI zeolite was used.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Cracking of hydrocarbon may be driven by formation of an intermediate of carbenium ion on solid acid sites. Usage of ns Al2O3 as a binder for high silica zeolite particle leads to formation of acid sites on the surface of the zeolite catalyst, to produce carbenium ions on the sites, and to promote the cracking reaction 19) . The basic structure of zeolite is a chain of tetrahedrons consisting of silicon cations, aluminum cations and oxygen anions.…”
Section: Effect Of Ns Oxide Species Of Tri-componentmentioning
confidence: 99%